Impact of equilibration on sperm quality in Malabari buck semen: A comparative study of different freezability levels - B. Vigneshwaran; Leeba Chacko; K. Promod; Renjith Sebastain; Magnus Paul K; Muhammed Aslam; Anupam Arun (Journal of Veterinary and Animal Sciences, 2025)
This study aimed to investigate the alterations in the sperm quality parameters across high and low freezability semen samples of Malabari bucks during post-extension and pre-freeze stages of cryopreservation. A total of 32 semen ejaculates with at least 80 per cent initial progressive motility were selected, categorising four bucks as high freezability and four as low freezability based on post-thaw characteristics. Significant variation was found in progressive motility at the pre-freeze stage, with high freezability samples showing a markedly higher motility (68.25 1.02 ) compared to low freezability samples (58.50 1.0 ), indicating that motility is closely linked to freezability. Sperm viability was higher in the high freezability group post-extension (91.2 0.56 ) and pre-freeze (79.70 0.60 ) than in the low freezability group (91.00 0.79 and 78.85 1.09 , p